Enantiomeric separation of novel anticancer agent 5-hydroxy-3-(4-methoxyphenyl)-2-(3,4,5-trimethoxyphenyl)-cyclopent-2-en- 1-one - Shinde, Popat D.; Jadhav, Vinod H.; Borate, Hanumant B.; Bhide, Sunil R.; Sonawane, Kiran B.; Wakharkar, Radhika D. (Journal of Chromatography A, 2007)
The enantiomers of 5-hydroxy-3-(4-methoxyphenyl)-2-(3,4,5-trimethoxyphenyl)-cyclopent-2-en- 1-one, a novel anticancer agent, were separated by derivatisation with caronaldehyde, separation of the resulting diastereoisomers of the corresponding esters by silica gel column chromatography and regeneration of alcohols (S)-5-hydroxy-3-(4-methoxyphenyl)-2-(3,4,5-trimethoxyphenyl)-cyclopent-2 -en-1-one and (R)5-hydroxy-3-(4-methoxyphenyl)-2-(3,4,5-trimethoxyphenyl)-cyclopent-2- en- 1-one under aqueous conditions. The absolute configuration of the enantiomers was determined by H-1 NMR studies of the corresponding Mosher esters. Alternatively, the enantiomers were separated by preparative HPLC to collect the (S)- and (R)-5-hydroxy-3-(4-methoxyphenyl)-2-(3,4,5-trimethoxyphenyl)-cyclopent-2 -en-1-ones with high purity which was comparable with that obtained by the chemical method. The details of these methods have been presented herein. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Anticancer; column chromatography; diaryl cyclopentenone; diastereoisomers; enantioseparation; HPLC; Resolution

Isolation, characterization and antihyperlipidemic activity of secoisolariciresinol diglucoside in poloxamer-407-induced experimental hyperlipidemia - Zanwar, Anand A.; Hegde, Mahabaleshwar V.; Rojatkar, Supada R.; Sonawane, Kiran B.; Rajamohanan, P. R.; Bodhankar, Subhash L. (Pharmaceutical Biology, 2014)
Context: Linum usitatissimum L. (Linaceae), commonly known as flaxseed, is a good source of dietary fiber and lignans. Earlier we reported cardioprotective, antihyperlipidemic, and in vitro antioxidant activity of flax lignan concentrate (FLC) obtained from flaxseed. Objectives: To isolate secoisolariciresinol diglucoside (SDG) from FLC and to evaluate the antihyperlipidemic activity of SDG in poloxamer-407 (P-407)-induced hyperlipidaemic mice. Material and methods: FLC was subjected to column chromatography and further subjected to preparative HPTLC to isolate SDG. The chemical structure of the isolated compound was elucidated by UV, IR, H-1 NMR, C-13 NMR, DEPT, COSY, HSQC, HMBC, ROESY, MS, and specific optical rotation was recorded. Further, we have investigated the antihyperlipidaemic effect of SDG (20 mg/kg) in P-407-induced hyperlipidaemic rats. Hyperlipidaemia was induced by intraperitoneal administration of P-407 (30% w/v). Serum lipid parameters such as total cholesterol (TC), triglycerides (TG), and high-density lipoprotein cholesterol (HDL-C) levels were measured. Results and discussion: The structure and stereochemistry of the isolated compound were confirmed on the basis of 1D and 2D spectral data and characterized as SDG. Finally, isolated pure SDG was screened using a P-407-induced mice model for its antihyperlipidemic action using serum lipid parameters. The isolated SDG (20 mg/kg) significantly reduced serum cholesterol, triglyceride (p<0.001), very low-density lipoprotein (p<0.05), and non-significantly increased HDL-C. Conclusion: Finally, it was concluded unequivocally that SDG showed antihyperlipidaemic effects in P-407-induced hyperlipidaemic mice. Isolated pure SDG confirms that SDG is beneficial in the prevention of experimental hyperlipidemia in laboratory animals.
Keywords: column chromatography; flaxseed; Linum usitatissimum

Lignin depolymerization into aromatic monomers over solid acid catalysts - Deepa, Ayillath K.; Dhepe, Paresh Laxmikant (ACS Catalysis, 2015)
It is imperative to develop an efficient and environmentally benign pathway to valorize profusely available lignin, a component of nonedible lignocellulosic materials, into value-added aromatic monomers, which can be used as fuel additives and platform chemicals. To convert lignin, earlier studies used mineral bases (NaOH, CsOH) or supported metal catalysts (Pt, Ru, Pd, Ni on C, SiO2, Al2O3, etc.) under a hydrogen atmosphere, but these methods face several drawbacks such as corrosion, difficulty in catalyst recovery, sintering of metals, loss of activity, etc. Here we show that under an inert atmosphere various solid acid catalysts can efficiently convert six different types of lignins into value-added aromatic monomers. In particular, the SiO2Al2O3 catalyst gave exceptionally high yields of ca. 60% for organic solvent soluble extracted products with 95 +/- 10% mass balance in the depolymerization of dealkaline lignin, bagasse lignin, and ORG and EORG lignins at 250 degrees C within 30 min. GC, GC-MS, HPLC, LC-MS, and GPC analysis of organic solvent soluble extracted products confirmed the formation of aromatic monomers with ca. 90% selectivity. In the products, confirmation of retention of aromatic nature as present in lignin and the appearance of several functional groups has been carried out by FT-IR and H-1 and C-13 NMR studies. Further, isolation of major products by column chromatography was carried out to obtain aromatic monomers in pure form and their characterization by NMR is presented. A detailed characterization of six different types of lignins obtained from various sources helped in substantiating the catalytic results obtained in these reactions. A meticulous study on fresh and spent catalysts revealed that the amorphous catalysts are preferred to obtain reproducible catalytic results.
Keywords: aromatic monomers; Biomass; column chromatography; depolymerization; lignin; solid acid catalysts